2016
DOI: 10.1155/2016/8014252
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fructose Activates Insulin Signaling and Inflammation in Adipose Tissue: Modulatory Role of Resveratrol

Abstract: The effects of high-fructose diet on adipose tissue insulin signaling and inflammatory process have been poorly documented. In this study, we examined the influences of long-term fructose intake and resveratrol supplementation on the expression of genes involved in insulin signaling and the levels of inflammatory cytokines and sex hormones in the white adipose tissues of male and female rats. Consumption of high-fructose diet for 24 weeks increased the expression of genes involved in insulin signaling includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 42 publications
(56 reference statements)
3
58
2
Order By: Relevance
“…In agreement with other reports, we also found an increase in inflammatory markers (IL-6, IL-1β and TNFα) and a decrease in anti-inflammatory markers (CD206: M2 marker and IL-10 ) in EAT from FRD mice [31,[47][48][49][50]. Moreover, adipocytes isolated from FRD mice showed an inflammatory response (higher IL-6 release) that worsened when the obese phenotype was more evident (FRD 10 weeks).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…In agreement with other reports, we also found an increase in inflammatory markers (IL-6, IL-1β and TNFα) and a decrease in anti-inflammatory markers (CD206: M2 marker and IL-10 ) in EAT from FRD mice [31,[47][48][49][50]. Moreover, adipocytes isolated from FRD mice showed an inflammatory response (higher IL-6 release) that worsened when the obese phenotype was more evident (FRD 10 weeks).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Under high fructose consumption, adipose tissue is the key site, giving rise to the secretion of inflammatory cytokines in systemic circulation [129]. Adipose dysfunction can disturb energy expenditure and insulin signaling mainly through inflammatory cytokines [130].…”
Section: Indirect Dangerous Factors In Tissue and Organ Dysfunctiomentioning
confidence: 99%
“…Namely, MIF can limit GCs effects, most likely through p38 phosphorylation, while the absence of endogenous MIF is associated with increased sensitivity to GCs through decreased phosphorylation of p38 MAPK (Calandra et al 1995, Aeberli et al 2006a. Proinflammatory p38 kinase is activated by oxidative stress and inflammation in 3T3-L1 cells and human adipocytes (Merkel et al 2002, Chuang et al 2010, Vazquez Prieto et al 2015, Cheng et al 2017, and fructose diet is known to enhance the production of proinflammatory cytokines and oxidative stress mediators in rodent visceral adipose tissue (Kovačević et al 2016, Pektas et al 2016. Our results showed that fructose diet indeed led to the elevation in both total and phospho p38 protein levels in WT and Mif-deficient mice.…”
Section: Figurementioning
confidence: 99%